Incarcerated subxiphoid eventration: a rare and potentially fatal pathology - Velayos García, Paula; Pascual Nadal, Juan José; Ripoll Martín, Roberto; Ots Gutiérrez, José Ramón; Oliver García, Israel (Cirugía del Uruguay, 2024)
This is an 89-year-old male patient, with a mitral prosthesis, who underwent surgery 20 years ago, and came to the emergency room due to abdominal pain and vomiting. A thoraco-abdominal computed tomography (CT) was performed, which confirmed the presence of subxiphoid eventration with parietal distress, requiring intestinal resection and eventhroplasty with intraperitoneal mesh. Subxiphoid eventration is a rare pathology, which mostly occurs in patients who have required interventions in the cardiac or hepatobiliopancreatic area. Its diagnosis is based on clinical symptoms and physical examination. This pathology represents a challenge for the surgeon given the surgical complexity of the anatomical region where it appears, since the adjacent chondrocostal structures make suturing and eventhroplasty difficult. In almost all series the repair has been selective, with emergency surgery due to incarceration being something anecdotal. The suggested technique would be preperitoneal eventhroplasty with non-absorbable retroxiphoid mesh; however, this is conditional on intraoperative findings, especially strangulation.